Expectativas de familiares de alcoolistas em diferentes estágios de tratamento acerca das intervenções do Caps ad - Carvalho, Maria de Fátima Alves Aguiar (2010)
Alcohol dependence has long ceased to be seen as a problem of individual nature, but should be conceived as a serious public health problem, whose increasingly voluminous negative repercussions can be seen in various sectors of society. Its social, psychological, economic and political implications are enormous and must be considered globally. The present paper is a descriptive study, developed on a qualitative perspective, which investigated the expectations of family members of alcoholics about the operations of CAPS ad in several stages of treatment. Nine members of nuclear families living with an alcoholic member were interviewed, which included the wives of alcoholics and nine of their 17 children. These families represent three groups, each consisting of three families. The first group consists of family members of incoming users (up to 3 months of treatment). The second group consists of families of intermediate users (those who are undergoing treatment for a period between 7 and 10 months). The third group consists of family members of veterans in terms of bonding with the CAPS ad (those who are in treatment for over a year). Data collection was conducted through semi-structured individual interview. Content analysis procedures were employed in the obtained data analysis. We verified that in the studied families, the expectations of family members who have joined the activities performed by CAPS ad revealed predominantly positive. As time goes by and the alcoholic continues in treatment, these expectations were getting stronger because in these cases there was an abstention or a pattern of eventual drinking, under control, with damage from abusive drinking being minimized (which may be different in each case, although some aspects are verified in all families). Among the nine participating families, there was only one which did not believe in the recovery of the dependent. We conclude that because of the diversity of factors that affect personal, family and social life of the alcoholic, of the constraints that the families find to deal with the issue in its own sphere, and considering the fact that the perception of these families about the role of CAPS ad is quite positive. It may be a promising way to think of intersectoral integral action, combined with various segments of society, thus enabling the formation of a care network with expanded resolving capacity